Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Toxicity and Safety Assessment of Key Pesticides Used in Rice Fields on Rice Flower Carp (Procypris merus) - Qianxue Shao; Yongming Ruan; Ru Liang; Ruixin Jin; Zhixi Jin; Lin Xie; Yongqing Chi; Jiaojiao Xia; Pingyang Zhu (Fishes, 2025)
Integrated rice–fish farming, crucial for sustainable agriculture, relies on the judicious use of pesticide. This study evaluates the toxicity of six common rice-field pesticides on Procypris merus (rice flower carp), a key species in these systems. We conducted acute and chronic toxicity tests, assessing survival, growth, oxidative stress (SOD, CAT, MDA, 8-OHdG), and neurotoxicity (AChE). Results revealed a spectrum of toxicity: abamectin and trifloxystrobin were highly toxic; pretilachlor was moderately so; and glufosinate-ammonium, triflumezopyrim, and thiazole zinc were low. Notably, triflumezopyrim induced significant oxidative stress and DNA damage, while all three low-toxicity pesticides inhibited AChE activity, indicating potential neurotoxicity. Despite these effects, all observed toxicities were reversible within 7–14 days. Considering that the tested concentrations exceeded typical field application rates, glufosinate-ammonium, triflumezopyrim, and thiazole zinc are deemed relatively safe for P. merus at recommended dosages. Our findings provide critical insights for optimizing pesticide selection in rice–fish farming, balancing pest control with ecological safety, thereby informing sustainable agricultural practices.

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Devosia lacusdianchii sp. nov., an attached bacterium inhibited by metabolites from its symbiotic Microcystis - Qing-Lin Deng; Yao Xiao; Ru Jia; Xin Xie; Le Wang; Xin Wang; Jian-Yuan Yang; Qi-Gen Guo; Bing-Huo Zhang (Antonie van Leeuwenhoek, 2024)

Most appropriate nozzle of six-rotor UAV for prescribed spraying liquid in tea plantation under effects of downwash flow structure in hover - Nai-Hong Hu; Wen-Xuan Zhou; Lin Zhu; Yan-Cheng Li; Xin-Yu Xie; Ru-Yan Hou; Cheng-Long Yin (Crop Protection, 2024)

Bacterial functions are main driving factors on paddy soil organic carbon in both surface soil and subsoil - Xiang-Wen Huang; Jia-Jun Lin; De-Jin Li; Xiang-Qi Huang; Qi-Huan Xie; Sheng-Gang Pan; Xiang-Ru Tang; Jian-Ying Qi (Agriculture, Ecosystems & Environment, 2024)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A novel oxygen vacancies enriched Co Ni LDO catalyst activated peroxymonosulfate for the efficient degradation of tetracycline - Hao-Liang Jiang; Ming-Hui Li; Ling-Xi Zhao; Zhao-Xing Yan; Meng Xie; Jin-Ming Lin; Ru-Song Zhao (Journal of Water Process Engineering, 2023)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

Biomimetic Au nanodot synthesis using Escherichia coli secretion and interaction with α-ketoglutaric acid - Xiaoxiao Xie; Xiaoli Yang; Yi Chang; Xiangli Ru; Xiaoming Ma; Lin Yang (Science China Life Sciences, 2021)

FW0622, a new siderophore isolated from marine Verrucosispora sp. by genomic mining - Wei Zhao; Fei Peng; Chuan-xi Wang; Yang Xie; Ru Lin; Zhi-kai Fang; Fei Sun; Yun-yang Lian; Hong Jiang (Natural Product Research, 2020)

Isolation, purification and identification of two new alkaloids metabolites from marine-derived Verrucosispora sp. FIM06025 - Ming-Hong Chen; Wen-Long Zhang; Li Chen; Ru Lin; Yang Xie; Dong-Sheng Fang; Yun-Yang Lian; Hong Jiang (Natural Product Research, 2019)

Structure elucidation and antitumour activity of a new macrolactam produced by marine-derived actinomycete Micromonospora sp. FIM05328 - Yi-Lei Nie; Yun-Dan Wu; Chuan-Xi Wang; Ru Lin; Yang Xie; Dong-Sheng Fang; Hong Jiang; Yun-Yang Lian (Natural Product Research, 2018)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Compounds from marine-derived Verrucosispora sp. FIM06054 and their potential antitumour activities - Nie Yi-Lei; Wu Yun-Dan; Wang Chuan-Xi; Lin Ru; Xie Yang; Fang Dong-Sheng; Jiang Hong; Lian Yun-Yang (Natural Product Research, 2014)

A study of shear strength properties of municipal solid waste in Chongqing landfill, China - Yan Ru Zhao; Qiang Xie; Gui Lin Wang; Yong Jian Zhang; Yong Xing Zhang; Wenjun Su (Environmental Science and Pollution Research, 2014)

Livin abrogates apoptosis of SPC-A1 cell by regulating JNKI signaling pathway - Yu-Sheng Chen; Hong-Ru Li; Ming Lin; Gang Chen; Bao-Song Xie; Neng-Luan Xu; Li-Fang Lin (Molecular Biology Reports, 2010)